Analysis of Goods Transportation Disputes: Cibinong District Court Decision Study - Firdaus Firdaus; Miskun Miskun; Upik Mutiara (Indonesian Journal of Law and Policy Studies, 2025)
International trade is inherently linked to international contracts, including freight forwarding agreements that regulate the rights and obligations of parties in cross-border shipping. In practice, such contracts often lead to disputes, either due to breach of obligations or procedural issues in law enforcement. One example is the Cibinong District Court Decision Number 239/Pdt.G/2020/PN Cbi involving Hakua Trading Co., Ltd. and PT Trinitan Metals and Minerals Tbk. This study examines the dispute by focusing on the legal standing of the parties, the object of the agreement, the role of the Bill of Lading, the application of Incoterms, and the judges’ legal considerations. Using a normative legal research method with statutory and case approaches, the study finds that the court did not examine the substance of the dispute due to procedural and jurisdictional issues. Consequently, the claim was declared inadmissible. The decision highlights the importance of clear contractual clauses and the proper determination of jurisdiction in resolving disputes arising from international freight forwarding contracts.